Modeling and simulation of temperature control system in plant factory using energy balance - Zhang, Mingqiu; Zhang, Wei; Chen, Xiaoyu; Wang, Fei; Wang, Hui; Zhang, Jisheng; Liu, Linhui (International Journal of Agricultural and Biological Engineering, 2021)
Closed production systems, such as plant factories and vertical farms, have emerged to ensure a sustainable supply of fresh food, to cope with the increasing consumption of natural resource for the growing population. In a plant factory, a microclimate model is one of the direct control components of a whole system. In order to better realize the dynamic regulation for the microclimate model, energy-saving and consumption reduction, it is necessary to optimize the environmental parameters in the plant factory, and thereby to determine the influencing factors of atmosphere control systems. Therefore, this study aims to identify accurate microclimate models, and further to predict temperature change based on the experimental data, using the classification and regression trees (CART) algorithm. A random forest theory was used to represent the temperature control system. A mechanism model of the temperature control system was proposed to improve the performance of the plant factories. In terms of energy efficiency, the main influencing factors on temperature change in the plant factories were obtained, including the temperature and air volume flow of the temperature control device, as well as the internal relative humidity. The generalization error of the prediction model can reach 0.0907. The results demonstrated that the proposed model can present the quantitative relationship and prediction function. This study can provide a reference for the design of high-precision environmental control systems in plant factories.Keywords: plant factory, temperature control system, mechanism simulation, random forest, cart model, generalization errorDOI: 10.25165/j.ijabe.20211403.6114Citation: Zhang M Q, Zhang W, Chen X Y, Wang F, Wang H, Zhang J S, et al. Modeling and simulation of temperature control system in plant factory using energy balance. Int J Agric & Biol Eng, 2021; 14(3): 66–75.